TEACHING ENGLISH FOR SPEECH USING COOPERATIVE LEARNING TO THE SECOND SEMESTER STUDENTS - Sinta S; Andika Andika (Esteem Journal of English Education Study Programme, 2023)
The title of this research is "Teaching English for Speech Using Cooperative Learning to Second Semester Students of ISB Atma Luhur Pangkal Pinang and Sjakhyakirti University". The formulation of the problem in this study: â€œIs cooperative learning effective in teaching English for Speech in the Second Semester? ISB Atma Luhur Pangkal Pinang and Sjakhyakirti University students?â€ The research method applied is experimental research. The experimental method applied is a quasi-experimental. The SPSS program is used to obtain experimental results. The statistical results between the experimental and control groups (t-obtained) must be higher than the t-table (0.05) for the two-tailed group, which is the result obtained based on data analysis. The students' scores for the control and experimental groups (the t-value obtained) were -10.325. The t value obtained is greater than the t table, the null hypothesis is rejected and the alternative hypothesis is obtained. It was found that teaching English in the use of speech by applying cooperative learning dialogue had better efficiency than the conventional method which was carried out in the second semester for students.